Ethanol levels in legally autopsied subjects: Analytical approach and epidemiological relevance in a prospective study in the touristic region of the Canary Islands (Spain) - Almeida-González, Maira; Henríquez-Hernández, Luis A.; P. Luzardo, Octavio; Zumbado, Manuel; Zaragoza, Enrique; Meilán, María J.; Camacho, María; D. Boada, Luis (Journal of forensic and legal medicine, 2017)
The aim of this study was to analyze the presence of alcohol in individuals (137) that were subjected to a mandatory medico-legal autopsy in the Institute of Legal Medicine of Las Palmas (Canary Islands, Spain) during 2015. Blood and vitreous humor samples (232) were analyzed by gas chromatography. 46.0% of the individuals were positive for alcohol, being half of them tourists. Blood alcohol concentrations (BAC) was higher in men over 60 years (p = 0.041). 10.2% of the series died in a traffic accident, and victims had the highest proportion of positives to alcohol (64.3%) and the highest BAC (2.56 g/L, p = 0.048). The BAC:VHAC (alcohol in vitreous humor) ratio was higher among victims of traffic crashes (p = 0.036), suggesting a short elapsed interval between the alcohol intake and the fatal accident. The results of this study indicate that ethanol is still heavily involved in non-natural deaths. •BAC and VHAC were determined in 232 samples from medico-legal autopsies.•Men over 60 years showed the highest BAC.•Highest BAC was observed among subjects died in a traffic accident.•The BAC:VHAC ratio was higher among victims of traffic crashes.